Los dispositivos institucionales y la cultura política como factor de la participación y el desarrollo territorial a escala local. - Olalla Vera Pastor (Cuadernos de Geografía de la Universitat de València)
The participation of the subjects in local development processes can be explained from two variables: the political and institutional incentives and political culture of the territory. They had the following study hypotheses: 1) in those areas characterized by political contexts that encourage local participation, there are better conditions for territorial development processes and participation of subjects, 2) in those areas marked with a political culture participatory, there are higher levels of local development. To corroborate the hypotheses, we carried out an investigation in the town of Meanguera, Morazán department, El Salvador. Thus, although we were facing a political context that nurtured local participation, some communities in the municipality appeared apathetic and indifferent to local development processes, which were detrimental to the development of their town. Explain what factors determine local participation is one of the main tasks of this article.